Clinical and immunological outcomes of SARS-CoV-2 infection in patients with inborn errors of immunity receiving different brands and doses of COVID-19 vaccines - İLKİ, ZEYNEP ARZU (My University, 2023)
Introduction: Vaccines against severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) provide successful control of the coronavirus-2019 (COVID-19) pandemic. The safety and immunogenicity studies are encouraging in patients with inborn errors of immunity (IEI); however, data about mortality outcomes and severe disease after vaccination still need to be fully addressed. Therefore, we aimed to determine the clinical and immunological outcomes of SARS-CoV-2 infection in patients with IEI who have received vaccination. Materials and Methods: Eighty-eight patients with a broad range of molecular etiologies were studied; 45 experienced SARS-CoV-2 infection. Infection outcomes were analyzed in terms of genetic etiology, background clinical characteristics, and immunization history, including the type and number of doses received and the time elapsed since vaccination. In addition, anti-SARS-CoV-2 antibodies were quantified using electrochemiluminescent immunoassay. Results: Patients were immunized using one of the three regimens: inactivated (Sinovac, Coronavac®), mRNA (BNT162b2, Comirnaty®, Pfizer-Biontech), and a combination. All three regimens induced comparable anti-SARS-CoV-2 IgG levels, with no differences in the adverse events. Among 45 patients with COVID-19, 26 received a full course of vaccination, while 19 were vaccine-naive or received incomplete dosing. No patients died due to COVID-19 infection. The fully immunized group had a lower hospitalization rate (23% vs. 31.5%) and a shorter symptomatic phase than the others. Among the fully vaccinated patients, serum IgM and E levels were significantly lower in hospitalized patients than non-hospitalized patients. Conclusion: COVID-19 vaccines were well-tolerated by the IEI patients, and a full course of immunization was associated with lower hospitalization rates and a shorter duration of COVID-19 symptoms.

Giriş: Şiddetli akut solunum sendromu koronavirüs-2 (SARS-CoV-2) aşıları koronavirüs (COVID-19) pandemisinin başarılı şekilde kontrol edilmesinde etkili olmuştur. İmmün sistemin doğuştan gelen kusurları (IEI) olan hastalarda aşıların güvenilirlik ve immünojenite çalışmaları ümit verici sonuçlar vermis olsa da aşı sonrası mortalite sonuçları ve hastalık şiddeti hakkındaki veriler henüz kısıtlıdır. Bu nedenle SARS-CoV-2 aşıları uygulanan IEI hastalarında SARS-CoV-2 enfeksiyonunun klinik ve immünolojik sonuçlarını değerlendirmeyi amaçladık. Materyal ve Metod: Kırk beşi SARS-CoV-2 enfeksiyonunu geçiren, farklı moleküler etiyolojiye sahip 88 IEI hastası çalışmaya dahil edildi. Enfeksiyon sonuçları, altta yatan genetik etiyoloji, klinik özellikler, uygulanan aşı doz sayısı, aşı markası ve aşılamadan hastalık oluşana kadar geçen süreye göre analiz edildi. Ayrıca anti-SARS-CoV-2 antikor düzeyleri elektrokemilüminesan yöntemi ile ölçüldü. Bulgular: COVID-19 geçiren 45 hastadan 26’sı tam doz aşılı iken, 19’u eksik doz ya da hiç aşı olmayan hastalardan oluşmaktaydı. Hastaların aşı şeması, inaktif (Sinovac, Coronavac®), mRNA (BNT162b2, Comirnaty®, Pfizer-BioNTech) ve iki aşının kombinasyonu olmak üzere üç farklı grupta değerlendirildi. Her üç grupta da benzer anti-SARS-CoV-2 antikor düzeyleri saptandı ve yan etki profili benzerdi. Tüm gruplarda COVID-19 enfeksiyonu ile ilişkili ölüm olmadı. Tam doz aşılı grupta hastane yatış oranı (%23’e karşı %31,5) ve semptomatik gün sayısı diğer gruba göre daha düşük idi. Tam doz aşılı olup hastane yatışı olanlarda serum IgM ve IgE düzeyleri hastaneye yatmayanlara kıyasla anlamlı olarak düşük saptandı. Sonuç: IEI hastalarında tam doz SARS-CoV-2 aşılaması iyi tolere edilir ve daha düşük oranda hastane yatışı ve daha az COVID-19 semptom süresiyle ilişkilidir
İmmün sistemin doğuştan gelen kusurları olan hastalarda farklı marka ve dozlarda uygulanan SARS-CoV-2 aşısı sonrası SARSCoV-2 enfeksiyonunun klinik ve immünolojik sonuçları
Keywords: Inborn errors of immunity; the Pfizer/BioNTech BNT162b2; Sinovac; SARS-CoV-2; COVID-19 vaccines; İmmün sistemin doğuştan gelen kusurları; Pfizer/BioNTech BNT162b2; COVID-19 aşıları